2019
DOI: 10.2337/dc19-0524
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gestational Diabetes Mellitus and Newborn DNA Methylation: Findings From the Pregnancy and Childhood Epigenetics Consortium

Abstract: OBJECTIVE Maternal gestational diabetes mellitus (GDM) has been associated with adverse outcomes in the offspring. Growing evidence suggests that the epigenome may play a role, but most previous studies have been small and adjusted for few covariates. The current study meta-analyzed the association between maternal GDM and cord blood DNA methylation in the Pregnancy and Childhood Epigenetics (PACE) consortium. RESEARCH DESIGN AND METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
5
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 39 publications
(57 reference statements)
4
87
5
4
Order By: Relevance
“…Results from a recent meta-analysis from seven pregnancy cohorts among 3677 mother-newborn pairs showed that gestational diabetes was not associated with differential methylation at a single CpG level, but it was associated with lower cord blood methylation levels within two specific regions [1]. In the current population-based EWASs, we did not find any associations in the full group, but maternal early-pregnancy glucose concentrations were associated with DNA methylation at cg03617420 (XKR6) among normal weight women, and at cg12081946 (IL17D) among overweight or obese women.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from a recent meta-analysis from seven pregnancy cohorts among 3677 mother-newborn pairs showed that gestational diabetes was not associated with differential methylation at a single CpG level, but it was associated with lower cord blood methylation levels within two specific regions [1]. In the current population-based EWASs, we did not find any associations in the full group, but maternal early-pregnancy glucose concentrations were associated with DNA methylation at cg03617420 (XKR6) among normal weight women, and at cg12081946 (IL17D) among overweight or obese women.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 99%
“…Previous studies using candidate-gene approaches suggested that maternal gestational diabetes is associated with epigenetic modifications in placenta and cord blood at loci relevant to growth, energy homeostasis, and diabetes mellitus [14,[16][17][18]. Epigenome-wide association studies (EWAS) of gestational diabetes or maternal glucose concentrations showed varying results, with no clear pattern of associations [1,15,[19][20][21][22][23][24][25]. The inconsistent results of candidate-gene studies and EWAS may be due to differences in study design.…”
Section: Introductionmentioning
confidence: 99%
“…Previous DNA methylation studies on cord blood found an association between GDM-induced changes in methylation and early childhood weight [50] and adiposity [51] or brain-related conditions including impairments in neurodevelopment [52] and child depression [53]. A large epigenome-wide DNA methylation study from the Pregnancy and Childhood Epigenetics (PACE) consortium was analyzed for an association between maternal GDM and cord blood methylation and showed that GDM is associated with lower methylation within two genes: the promoter of OR2L13, a gene associated with autism, and the gene body of CYP2E1, which encodes WHAT and is upregulated in type 1 and type 2 diabetes [54]. Similar findings were published by Weng et al, who showed that exposure to GDM results in changes in the methylation of cord blood cell genes which are strongly linked to type 1 diabetes mellitus, as well as neuronal development-related pathways associated with depression, attention deficit hyperactivity disorder, autism and intellectual impairment [55].…”
Section: Screening For Gdm-induced Epigenetic Modifications At Birthmentioning
confidence: 99%
“…Maternal undernutrition [17] and micronutrient status [18], maternal obesity [19,20], and socioeconomic status [21] have all been associated with changes in the methylation status of the offspring epigenome. Both candidate gene [22][23][24] and genome-wide studies [25][26][27][28][29][30][31] have reported that GDM exposure is associated with significant changes in the infant's or child's methylome, and a recent meta-analysis of 7 pregnancy cohorts identified differentially methylated regions (DMRs) associated with GDM within OR2L13 and CYP2E1 [32]. However, the majority of these studies have focussed on GDM versus no GDM, rather than the continuous relationship between maternal glucose levels and DNA methylation [33,34], and none has studied the GDM-associated signal within a high-risk population of women with obesity; thus, the relationship between the degree of maternal dysglycaemia and the contribution of maternal post-challenge/postprandial glucose excursions to the infant's methylation signature in this high-risk group remains unknown.…”
Section: Introductionmentioning
confidence: 99%